Biological Threats as Emerging Challenges in Modern Military Biodefense - Nizamuddin Ubaidillah (The ASEAN Journal of Military and Preventive Medicine, 2024)
A biological threat refers to an infectious disease with the potential to spread and cause an outbreak. The challenges posed by rapidly changing and increasingly complex biological threats became apparent after the global COVID-19 pandemic, leading to a decline in the preparedness of nations and sluggish responses. Despite the potential severity of casualties, military readiness should be the first line of defense, emphasizing deep prevention. The role of the military in overcoming threats becomes an urgency that cannot be avoided and must be an integral part of the handling of biological threats nationally.